PERMASALAHAN PEMBIAYAAN PADA LEMBAGA KEUANGAN SYARIAH - Gunawan, Karebet (MALIA: Journal of Islamic Banking and Finance, 2017)
Financing of a Sharia Financial Institution is a financing based on sharia principles with agreement or agreement between the banking party and the beneficiary in return for profit or profit sharing. In the provision of financing, sharia financial institutions pay attention to the aspects that exist in the feasibility study in order to reduce the risk in the future. These aspects are production, marketing, personnel, and financial aspects include how the existing financial statements so that all financing is expected to run smoothly and can meet the level of profitability and liability. In providing financing should be seen 5C principles are: character, capacity, capital, colateral and condition of economy. Even in addition to using the 5C there are also using the first 7P Personality, Purpose, Party,Prospect,Payment,Profitability,Protectiona. Keywords:financing,feasibility,and profitablity